Comparison of Adaptive Functioning in Children with Williams Beuren Syndrome and Autism Spectrum Disorder: A Cross‐Syndrome Study. Issue 4 (11th December 2020) - Alfieri, Paolo; Scibelli, Francesco; Digilio, Maria C.; Novello, Roberta L.; Caciolo, Cristina; Valeri, Giovanni; Vicari, Stefano
Abstract : Williams Beuren syndrome (WBS) and autism spectrum disorder (ASD) have been long considered as "polar opposite" disorders. Although children with WBS appears to be hypersociable, recent researches have revealed difficulties in socio‐communicative skills such as shared attention, showing or giving objects, social relationships comprehension, pragmatic use of language, and emotion's recognition. The aim of this cross‐syndrome study is to compare clinician‐report adaptive profiles of two wide developmental range children by means of Vineland Adaptive Behavior Scales—Interview Edition, Survey Form. Eighty individuals, 40 with WBS and 40 with ASD (31 preschoolers and 49 scholars) with ASD and WBS matched for chronological age and developmental/cognitive level were recruited. Analysis of domains and subdomains have been reported. Results showed no significant difference in global adaptive level between WBS and ASD in both preschooler and scholar children. Communication domain significantly differ in preschoolers (higher in WBS children), but not in scholars. Expressive subdomain significantly differ in both preschoolers and scholars (higher in WBS children). Play and Leisure subdomain significantly differ in scholars (higher in WBS children), but not in preschoolers. Our results support hypothesis on a shared global adaptive impairment in children with WBS and ASD, by extending this findings to scholar‐age children. Analysis of domains and subdomains differences highlight the need for interventions targeting social‐pragmatic skills since first years of life. Differences in preschoolers and scholars adaptive profiles could be explained through a developmental perspective. Lay Summary: Little is known about differences in adaptive profiles between Williams Beuren syndrome and autism spectrum disorder. Our results show similarities in global adaptive level and difference in communication level. Furthermore, expressive skills seem to be higher in Williams Beuren Syndrome. Autism Res 2021, 14: 748–758 . © 2020 International Society for Autism Research and Wiley Periodicals LLC